BRAF inhibition increases TGFβ2 production and stimulates metastasis in mice with endogenous BRAF V600E -induced hepatocellular carcinoma - Jaroslaw Cisowski; Ahmed Ezat El Zowalaty; Sama I. Sayin; Piotr Czarnota; Tomasz Gromowski; Ella A. Eklund; Muhammad Kashif; Angana A. H. Patel; Antonio Molinaro; Per Lindahl; Clotilde Wiel; Volkan I. Sayin; et al. (Proceedings of the National Academy of Sciences, 2025)
The MEK–ERK pathway is a key driver of hepatocellular carcinoma (HCC) pathogenesis, and BRAF mutations, particularly BRAF V600E , can contribute to its activation. Although BRAF V600E mutations are rare in human HCC, they do occur, yet their physiologic impact in liver cells, especially when combined with frequent comutations in tumor suppressor genes, remains poorly understood. Moreover, the effect of BRAF inhibitors on HCC progression and metastasis is not well-defined. Therefore, we developed mouse models with hepatocyte-specific BRAF V600E expression and Trp53 or Cdkn2a deletion to assess tumor development, subtypes, and metastatic patterns. We found that BRAF V600E expression caused hepatomegaly, vascular congestion, and ductal reactions, and led to reduced liver function and early mortality. Codeletion of Trp53 or Cdkn2a markedly increased primary liver tumor incidence and enabled sarcomatoid metastasis. While the BRAF inhibitor PLX4720 effectively reduced primary tumors and extended survival, it paradoxically increased sarcomatoid metastases. Mechanistically, PLX4720 and other RAF inhibitors induced TGFβ2 expression which promoted epithelial-to-mesenchymal transition (EMT) and enhanced tumorigenicity. The effects of RAF inhibitors on TGFβ2 expression were validated in BRAF V600E -mutant human melanoma cells. We conclude that BRAF V600E drives diverse primary tumors but only one type of metastasis and that RAF inhibition, while effective against primary tumors, may promote metastasis through TGFβ2-mediated EMT. Although RAF inhibitors remain promising therapies, their unintended role in enhancing metastasis raises concerns that may extend beyond liver cancer to other BRAF V600E -driven malignancies.